Penggunaan Media Bergambar Tuts Piano untuk Meningkatkan Teknik Bermain Piano - Kuncoro, Kuncoro (Paedagogie, 2020)
The use of illustrated media of piano keys to improve learning outcomes for Class X MIPA 6 SMA Negeri 1 Purwareja Klampok Academic Year 2019/2020 ". This research was carried out with the aim of describing how much improvement in the material applied to the pictorial media of piano keys with student learning outcomes and to describe changes in student attitudes (attention, activeness and responsibility) in increasing the basic competencies of playing piano techniques for Class X MIPA - 6 students. This classroom action research was conducted in two cycles. The results showed that there was an increase in the percentage of student learning outcomes, in the pre-cycle it was only 44.5%, while after learning for the first cycle the percentage of student learning increased from 44.5 to 86% and for an increase in learning achievement in cycle II was 100%. . Learning using pictorial media in this case is piano keys can also improve behavior or effectiveness of students to be more enthusiastic and active so that communication between students is well established and makes students have the character of a sense of responsibility, discipline, hard work and respect for the opinions of friends. Based on these data, it can be concluded that there was a significant increase in learning outcomes before using the piano key-illustrated media learning model, both in cycle I and cycle II. This is because the pictorial learning model can provide new experiences to students so that students can explore individual abilities with existing facilities. There was a change in the positive behavior of students from cycle I to cycle II when learning took place, students respected more what should be done and what should not be done, such as student attention, questioning responses, taking notes, group discussion activities, and not bothering friends who Finally, it affects the level of self-confidence of students to be able to play the piano in a relaxed, relaxed manner and in accordance with the rules of playing piano techniques.